Maternal–Neonatal Raltegravir Population Pharmacokinetics Modeling: Implications for Initial Neonatal Dosing. (10th July 2019) - Lommerse, Jos; Clarke, Diana; Kerbusch, Thomas; Merdjan, Henri; Witjes, Han; Teppler, Hedy; Mirochnick, Mark; Acosta, Edward P.; Wenning, Larissa; Nachman, Sharon; Chain, Anne
Abstract : Raltegravir readily crosses the placenta to the fetus with maternal use during pregnancy. After birth, neonatal raltegravir elimination is highly variable and often extremely prolonged, with some neonates demonstrating rising profiles after birth despite removal from the source of extrinsic raltegravir. To establish an appropriate dosing regimen, an integrated maternal–neonatal pharmacokinetics model was built to predict raltegravir plasma concentrations in neonates with in utero raltegravir exposure. Postnatal age and body weight were used as structural covariates. The model predicted rising or decreasing neonatal elimination profiles based on the time of maternal drug administration relative to time of birth and degree of in utero drug disposition into the central and peripheral compartments. Based on this model, it is recommended to delay the first oral dose of raltegravir until 1–2 days of age in those neonates born to mothers who received raltegravir during pregnancy, labor, and delivery.